A prospective study of outcome of double pigtail catheter drainage in the management of breast abscess: analysis of outcome - Prasad, Dinesh; Kalaria, Darshit; Satani, Yogesh (International Surgery Journal, 2021)
Background: Breast abscesses, localized collection of pus in the breast, are most common in young lactating women. Traditional treatment of breast abscesses is by surgical incision, digital disruption of septa, evacuation of contents with occasional placement of surgical drains, and administration of systemic antibiotics. Percutaneous large-bore needle aspiration with or without ultrasound guidance is generally employed as the first line treatment of breast abscesses. It is generally done for medium to large sized unilateral abscesses and requires repeated aspirations for complete resolution of the abscess cavity. Methods: We have conducted this prospective study at SMIMER Hospital, Surat, Gujarat, India from January 2020 to January 2021. After ethical approval a group of 25 patients with unilateral breast abscesses irrespective of the lactational status were treated by percutaneous double catheter drains inserted under ultrasound guidance under the effect of local anaesthesia and evaluated for 3 months. Results: The resultant cosmetic effect was good, with no reported recurrence on 3 month follow-up. Conclusions: Double pigtail catheter drainage in appropriately selected cases of beast abscess has superior outcome in compare to published result of other technique for drainage of beast abscess specially in minimal scarring, early resolution of abscess cavity and decreases in the total duration of treatment.